DESIGN OF H-PLANE SECTORAL HORN ANTENNA FOR MICROWAVE APPLICATIONS USING MATLAB - Abdulhussain Shuriji, Mushreq (Journal of Engineering and Sustainable Development, 2018)
Wireless communications has become more essential in our life, as well as considered as the one of fastest growing segment in the communication business. The antenna was and still the main component of any wireless communication system. In other word the antenna is the eyes and ears of any wireless communication system. Many recent research has carried out designing of H-sectoral horn antenna but yet H-plane horn antenna with a very high gain and narrow radiation pattern while keeping up its compact size is not been completely delivered. Consequently, H-plane sectoral horn operates on c-band (6GHz) has clarified and successfully designed using MATLAB with an optimum compact size. In addition, the power pattern of E-plane and H-plane have drawn using MATLAB simulation. In conclusion, the designed H-sectoral horn antenna is promising a directive, narrow and intense radiation in the direction of a selected path to support high coverage distances. Besides, a very high power of 21dB of gain is achieved. This antenna is perfectly suitable to use in numerous microwave applications such as, feed element in large radio astronomy, satellite tracking, feed for various lenses and reflectors antenna, and gain measurement for other transmitting antenna.